Dynamic changes in O-GlcNAcylation regulate osteoclast differentiation and bone loss via nucleoporin 153 - Li, Yi-Nan; Chen, Chih-Wei; Trinh, Minh Thuong; Zhu, Honglin; Matei, Alexandru-Emil; Györfi, Andrea-Hermina; Kuwert, Frederic; Hubel, Philipp; Ding, Xiao; Tran Manh, Cuong; Xu, Xiaohan; Liebel, Christoph; et al. (Bone Research, 2022)
Bone mass is maintained by the balance between osteoclast-induced bone resorption and osteoblast-triggered bone formation. In inflammatory arthritis such as rheumatoid arthritis (RA), however, increased osteoclast differentiation and activity skew this balance resulting in progressive bone loss. O-GlcNAcylation is a posttranslational modification with attachment of a single O-linked β-D-N-acetylglucosamine (O-GlcNAc) residue to serine or threonine residues of target proteins. Although O-GlcNAcylation is one of the most common protein modifications, its role in bone homeostasis has not been systematically investigated. We demonstrate that dynamic changes in O-GlcNAcylation are required for osteoclastogenesis. Increased O-GlcNAcylation promotes osteoclast differentiation during the early stages, whereas its downregulation is required for osteoclast maturation. At the molecular level, O-GlcNAcylation affects several pathways including oxidative phosphorylation and cell-cell fusion. TNFα fosters the dynamic regulation of O-GlcNAcylation to promote osteoclastogenesis in inflammatory arthritis. Targeted pharmaceutical or genetic inhibition of O-GlcNAc transferase (OGT) or O-GlcNAcase (OGA) arrests osteoclast differentiation during early stages of differentiation and during later maturation, respectively, and ameliorates bone loss in experimental arthritis. Knockdown of NUP153, an O-GlcNAcylation target, has similar effects as OGT inhibition and inhibits osteoclastogenesis. These findings highlight an important role of O-GlcNAcylation in osteoclastogenesis and may offer the potential to therapeutically interfere with pathologic bone resorption.
CRIS-Team Scopus Importer:2022-08-05

Fibroblast growth factor receptor 3 activates a network of profibrotic signaling pathways to promote fibrosis in systemic sclerosis - Chakraborty, Debomita; Zhu, Honglin; Juengel, Astrid; Summa, Lena; Li, Yi-Nan; Matei, Alexandru-Emil; Zhou, Xiang; Huang, Jingang; Thuong Trinh-Minh; Chen, Chih-Wei; Lafyatis, Robert; Dees, Clara; et al. (Science Translational Medicine, 2020)
Aberrant activation of fibroblasts with progressive deposition of extracellular matrix is a key feature of systemic sclerosis (SSc), a prototypical idiopathic fibrotic disease. Here, we demonstrate that the profibrotic cytokine transforming growth factor. selectively up-regulates fibroblast growth factor receptor 3 (FGFR3) and its ligand FGF9 to promote fibroblast activation and tissue fibrosis, leading to a prominent FGFR3 signature in the SSc skin. Transcriptome profiling, in silico analysis and functional experiments revealed that FGFR3 induces multiple profibrotic pathways including endothelin, interleukin-4, and connective tissue growth factor signaling mediated by transcription factor CREB (cAMP response element-binding protein). Inhibition of FGFR3 signaling by fibroblast-specific knockout of FGFR3 or FGF9 or pharmacological inhibition of FGFR3 blocked fibroblast activation and attenuated experimental skin fibrosis in mice. These findings characterize FGFR3 as an upstream regulator of a network of profibrotic mediators in SSc and as a potential target for the treatment of fibrosis.
CRIS-Team WoS Importer:2020-10-16

TGFβ promotes fibrosis by MYST1-dependent epigenetic regulation of autophagy - Zehender, Ariella; Li, Yi-Nan; Lin, Neng Yu; Stefanica, Adrian; Nüchel, Julian; Chen, Chih-Wei; Hsu, Hsiao Han; Zhu, Honglin; Ding, Xiao; Huang, Jingang; Shen, Lichong; Györfi, Andrea-Hermina; et al. (Nature Communications, 2021)
Activation of fibroblasts is essential for physiological tissue repair. Uncontrolled activation of fibroblasts, however, may lead to tissue fibrosis with organ dysfunction. Although several pathways capable of promoting fibroblast activation and tissue repair have been identified, their interplay in the context of chronic fibrotic diseases remains incompletely understood. Here, we provide evidence that transforming growth factor-β (TGFβ) activates autophagy by an epigenetic mechanism to amplify its profibrotic effects. TGFβ induces autophagy in fibrotic diseases by SMAD3-dependent downregulation of the H4K16 histone acetyltransferase MYST1, which regulates the expression of core components of the autophagy machinery such as ATG7 and BECLIN1. Activation of autophagy in fibroblasts promotes collagen release and is both, sufficient and required, to induce tissue fibrosis. Forced expression of MYST1 abrogates the stimulatory effects of TGFβ on autophagy and re-establishes the epigenetic control of autophagy in fibrotic conditions. Interference with the aberrant activation of autophagy inhibits TGFβ-induced fibroblast activation and ameliorates experimental dermal and pulmonary fibrosis. These findings link uncontrolled TGFβ signaling to aberrant autophagy and deregulated epigenetics in fibrotic diseases and may contribute to the development of therapeutic interventions in fibrotic diseases.
CRIS-Team Scopus Importer:2021-08-06